MSME Jatirejo: Together With KKN MB Posko 10 UIN Walisongo Semarang, Exploring the Diversity of MSME Products in the Tourism Village of Jatirejo Subdistrict. : Study in the Thematic Village, Jatirejo District - Muhammad Farhan Thirafi; Dely Puspita Ayu Kusno Putri; Zakia Hasna Azizah; Zahwa Alfis Fatayatul Masitoh; Muhammad Adib Mahsun; Chusnul Adib Achmad (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research discusses the economic potential and creativity of the community in Jatirejo Village, particularly through thematic approaches and Micro, Small, and Medium Enterprises. (MSME). The village of Jatirejo is famous for its various themes, including the Thematic Village of Kolang-Kaling (KOKOLAKA) in RW 1, which has become the icon of the area. The KOKOLAKA Village has 11 businesses processing kolang-kaling, including candied treats, crackers, meatball tofu, and Nasi Guling, which is a signature cuisine of Jatirejo. In addition, Jatirejo Village also has the Chili Pepper Thematic Village (KAMBERA) in RW 2, the Red Ginger Thematic Village (KAJERA) in RW 3, and the Green Fresh Farm (GFF) in RW 4. This culinary diversity not only meets daily food needs but also becomes a product that can be exported to other regions. This research also emphasizes the importance of digital marketing strategies to enhance sales and the popularity of MSME products, as well as identifying the challenges they face. Thus, Jatirejo Village can be said to be one of the areas with strong economic potential and high creativity, with various thematic types and small and medium enterprises (MSMEs) that demonstrate the local community’s dedication to developing the local economy and improving the quality of life for its residents.